Dealing with Divisiveness: Ignatian Principles for Better Relationships - Plante, Thomas G. (Pastoral psychology, 2025)
Interpersonal and intergroup relationships seem to have steadily deteriorated in recent years, with an increase in the lack of civility and decency along with a greater willingness to attack and cancel anyone who does not agree with one’s cherished perspective on numerous matters. New popular phrases such as cancel culture, public shaming, air rage, and gaslighting have entered the common vernacular. Ignatian spirituality offers several helpful strategies for dealing with these contemporary divisive conflicts in a productive manner. These include (1) seeing God (or the sacred) in all things, (2) striving towards kinship with others through the pathway of civility, hospitality, and solidarity, and (3) managing conflict with accommodation, humility, and the expectation of goodness in mind. This article introduces and provides examples of these three Ignatian principles that can be employed in all challenging relationships, including both personal and professional as well as psychotherapeutic ones. They can be utilized in a secular or spiritually minded manner as well. Having more tools to improve relationships is especially needed now.